Pengaruh Kehilangan Gigi Insisivus Desidui Atas Terhadap Pengucapan Fonem Bidental, Labiodental dan Linguodental Dalam Bentuk Morfem (Kajian Hasil Perekaman Suara Pada Anak Usia 4-6 tahun di TPA Al-Ikhlas, Komplek Pemadam Kebakaran, Kelurahan Joglo, Kecamatan Kembangan, Jakarta Barat) - , ARZELIA YORIKA LINANDO, drg. Rinaldi Budi Utomo, S.U., Sp. KGA(K). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Incisors are important organ for speech production. The loss of maxillary primary incisor can distract the articulation of bidental phoneme (/s/), labiodental phoneme (/f/) and linguodental phoneme (/t/). The purpose of this research is to observe the effect of maxillary primary incisors loss to the articulation of these phonemes using the voice frequency value analysis. The subject of this research were children, aged 4-6 years old, and students of TPA Al-Ikhlas Jakarta. Subjects were divided in two groups, the first group consists of children with normal maxillary primary incisors and the second group consists of children with four maxillary primary incisors loss. The subjectsâ voice were recorded while they say the word that consists morphemes with one of these three phonemes. Each phonemes was put in the initial, middle and final of word. The frequency value was obtained by analizing the recording results using Cool Edit Software. Data was analized with Independent t-test and Mann-Whitney test. The results showed that group with normal maxillary incisors had larger voice frequency value rather than group with maxillary primary incisor loss. There were significant difference (p<0.05) in the articulation of phoneme /t/ which was at the initial, middle and final of words